The (Re)Invention of Acting - Čale Feldman, Lada (2007)
The paper discusses the applicability of current paradigms of acting theory in the light of a recent theatre and media event in Croatia involving the engagement of a pop-folk celebrity in a state-sponsored National theatre production.